The Past, Present, and Future of Monkeypox: A Rapid Review Regarding Prevalence and Prevention - Waniyah Masood MBBS; Hira Anas Khan MBBS; Huzaifa Ahmad Cheema MBBS; Abia Shahid MBBS; Wajeeha Bilal MBBS; Manar Ahmed Kamal MBBCh; Mohammad Yasir Essar DMD; Shoaib Ahmad MBBS; Roy Rillera Marzo MPH, MBA (SAGE Publishing, 2022)
While monkeypox virus (MPXV) remained endemic in central and western African countries, a sudden unusual spike of global cases among non-endemic countries is an enigma for scientists. With 257 cases reported as of 26th May 2021, a multi-country outbreak of monkeypox has been declared in countries including the UK, EU/EEA states, and North America. Even though the likelihood of transmissibility of MPXV is limited compared to COVID-19, yet a coordinated multidisciplinary effort is required to prevent any further global expansion. Few appropriate responsive approaches to contain the infection could be; limiting the contact with potential animal reservoirs, isolation of confirmed cases, using PPEs to prevent human-human transmission, awareness activities, and administration of pre and post prophylactic vaccination. In this review, we have discussed the previous and current outbreaks of MPXV along with the abrupt actions that are needed to address the situation.